1993
DOI: 10.1093/nar/21.21.4975
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation by N-methyl-N-nitrosourea: methylation pattern changes in single- and double-stranded DNA, and in DNA with mismatched or bulged guanines

Abstract: The detection of abnormal DNA base pairing arrangements and conformations is chemically probed in synthetic 32P-end-labeled deoxyribonucleotide oligomers using N-methyl-N-nitrosourea (MNU) and 2,12,-dimethyl-3,7,11,17-tetraazabicyclo-[11.3.1]heptadeca-1 -[17],2,11,13,15 pentaene-Ni (II) (Ni-complex) with KHSO5. The DNA targets studied are single-stranded (s-s) DNA, double-stranded (d-s) DNA, d-s DNA with G-G, G-A and G-T mismatches, d-s DNA with a single bulged G and d-s DNA with two bulged G's. The effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…We observed that DNA damage induced by MNU or NDMAOAc is sequence-specific in a run of three or more guanines in purified DNA and in cellular DNA ( Figure 5). Our results, and those realized by other investigators, confirm that the sequence specificities of S N 1 agents are different from those of S N 2 agents ( Figure 5) (12)(13)(14)(15)33). S N 1 methylating agents (MNU and NDMAOAc) preferentially methylate the central guanines in a run of three or more guanines.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We observed that DNA damage induced by MNU or NDMAOAc is sequence-specific in a run of three or more guanines in purified DNA and in cellular DNA ( Figure 5). Our results, and those realized by other investigators, confirm that the sequence specificities of S N 1 agents are different from those of S N 2 agents ( Figure 5) (12)(13)(14)(15)33). S N 1 methylating agents (MNU and NDMAOAc) preferentially methylate the central guanines in a run of three or more guanines.…”
Section: Discussionsupporting
confidence: 83%
“…The yield of methylation by MNU is actually enhanced in double-stranded DNA versus singlestranded DNA, indicating that steric factors are not significant in this process (33). Metha et al (36) showed that MNU alone, or coupled with a specific major groove intercalator agent, might be hydrolyzed in the major groove, and increased the extent of N7-guanine methylation as shown by the ratio of N7-methylguanine (a major groove lesion) to N3-methyladenine (a minor groove lesion).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the requirement for a canonical double helix, a G that is mispaired with G, T or A becomes less reactive than a G paired with C ( Figure 5) (47). Similarly, the creation of G's in a single or double bulge show a decrease in alkylation ( Figure 5).…”
Section: Effect Of Dna Structure and Conformation On Alkylation Reactionsupporting
confidence: 54%
“…The pattern observed in ds-DNA is lost in ss-DNA, and most importantly, the alkylation yield was significantly reduced ( Figure 5) (47). In contrast, DMS, which shows no sequence selectivity with either ss-or ds-DNA, reacts more efficiently with the former.…”
Section: Effect Of Dna Structure and Conformation On Alkylation Reactionmentioning
confidence: 96%
“…In comparison to another S N 2-methylating agent MMS, the ratio for DMS is a slightly higher than was found for MMS (N7-/O 6 -MeG ratio = 200) [40]. The above ratio appear to depend on particular reacting conditions (aqueous solution, pH, duration incubation), but not on the double-or single-strandedness of DNA [41,42].…”
Section: Determination Of Methylated Adducts N3-mea N7-meg and O 6 -Megmentioning
confidence: 71%